Pengaruh Talent Management dan Retensi Karyawan terhadap Kinerja Karyawan dengan Knowledge Management sebagai Pemediasi pada Karyawan Minimarket di Jakarta - Joko Ariawan (Neolectura, 2022)
This study aims to analyze the effect of talent management, employee retention and knowledge management on performance with knowledge management as a mediating variable. The respondents of this study were 100 minimarket employees in Jakarta who were selected using purposive sampling, from February 2022 to May 2022. The data collected was processed using the path analysis method with the help of AMOS software. The results of the study conclude that talent management has a significant effect on knowledge management, retention has a significant effect on knowledge management, knowledge management does not affect the performance of minimarket employees in Jakarta, talent management has a significant effect on performance, and knowledge management has no effect on mediating talent management and employee retention.